Kharisma Kharisma Kiai dalam Dunia Politik (Telaah Buku “Kiai di Tengah Pusaran Politik Antara Petaka dan Kuasa”) - Moh. Romdhan; Abdul Wahid Hasan (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2023)
The existence of a charismatic individual (kiai) who dared to enter politics served as the inspiration for our study. In the current reality, the kiai is a person who the public knows as the nation's education generator rather than a politician who is infamously known for lying and frequently running on empty campaign promises. This study aims to define politics, define politics from an Islamic perspective, and define the charisma of the kiai in the political world. The findings of this study portray a charismatic kiai who dared to enter the field of practical politics. His decision, however, will present him with significant obstacles, leaving him with only two options. either he made a terrible choice or ended up gaining power. In addition to being a source of education, the kiai-politician also plays the important roles of being a politician who is susceptible to the allures of wealth and power. Due to this reality, the kiai must refrain from taking the initiative; instead, he must work as a motivating force behind the scenes without getting involved in politics. So that he won't lose his charisma and dignity, the kiai will be protected from all slander and accusations that can come his way. In addition, the community will always consider him a uswatun hasanah, which will be kept in their hearts for all time.